Evaluasi Dampak Pembangunan Pariwisata Menggunakan Konsep Community Based Tourism (CBT) di Kawasan Wisata Tebing Breksi - Nurwanto, Nurwanto (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2021)
Nowadays the development of tourism in an area will bring a positive impact on the local society. However, if the community is not ready to accept development and is not ready to manage its property, it will have a negative impact. Various problems will arise with the existence of mass tourism which makes it difficult or even detrimental to the community. Therefore, this study will discuss the evaluation of the impact tourism development in Tebing Breksi using the concept of community-based tourism (CBT). CBT is a development strategy that uses tourism as a tool to strengthen local communities that are managed by, from, and for the community, as well as considering aspects of sustainability to improve people’s welfare. The research method used is qualitative using a case study approach. The data used is sourced from primary data and secondary data. Primary data obtained by interviewing speakers who are considered competent in their fields and following the research topic. Secondary data were obtained from previous studies, documentation, a note, and an activity report related to Tebing Breksi. Evaluation of CBT principles at Tebing Breksi is seen based on five aspects, that is (i) Economic principles (ii) Social principles (iii) Cultural principles (iv) Environmental principles (v) Political principles, along with indicators. The result of the analysis shows that the principles of CBT applied at Tebing Breksi as a whole have shown success even though some of the indicators of the CBT principle need to be optimized again, while the positive impact obtained by the community with the presence of this CBT is increased economic income, improved quality of life, concern for waste management and mutual respect between cultures. Also, the success of CBT cannot be separated from the active role of community and government support.